Lie symmetry analysis and explicit solutions for the time fractional generalized Burgers-Huxley equation - İnç, Mustafa; Yusuf, Abdullahi; Aliyu, Aliyu Isa; Baleanu, Dumitru (Springer, 2018)
In this work, we study the time fractional generalized Burgers-Huxley equation with Riemann-Liouville derivative via Lie symmetry analysis and power series expansion method. We transform the governing equation to nonlinear ordinary differential equation of fractional order using its Lie point symmetries. In the reduced equation, the derivative is in Erdelyi-Kober sense. We apply power series technique to derive explicit solutions for the reduced equation. The convergence of the obtained power series solutions are also derived. Some interesting Figures for the obtained solutions are presented.
Keywords: Generalized Burgers-Huxley equation; Lie symmetry method; Power series technique; Explicit series solutions; Convergence analysis